One-pot Cannizzaro cascade synthesis of ortho-Fused Cycloocta-2,5-dien-1-ones from 2-Bromo(hetero)aryl aldehydes - Burroughs, Laurence; Eccleshare, Lee; Ritchie, John; Kulkarni, Omkar; Lygo, Barry; Woodward, Simon; Lewis, William (Wiley-VCH Verlag, 2015)
An intramolecular Cannizzaro-type hydride transfer to an in situ prepared allene enables the synthesis of orthofused 4-substituted cycloocta-2,5-dien-1-ones with unprecedented technical ease for an eight-ring carboannulation. Various derivatives could be obtained from commercially available (hetero)aryl aldehydes, trimethylsilylacetylene, and simple propargyl chlorides in good yields.